Efficacy and Safety of Lenalidomide Monotherapy for Relapsed/Refractory Diffuse Large B Cell Lymphoma: Systematic Review and Meta-Analysis - Li, Jia; Zhou, Jianpeng; Guo, Wei; Wang, Xingtong; Zhao, Yangzhi; Bai, Ou (Frontiers in Oncology, 2021)
Introduction: Several maintenance therapies are available for treatment of patients with relapsed/refractory (R/R) diffuse large B cell lymphoma (DLBCL). The objective of this review was to assess the efficacy and safety of lenalidomide monotherapy in these patients. Methods: MEDLINE, EMBASE, and the Cochrane Library databases were searched for publications up to April 7, 2021. Original studies that had information on lenalidomide monotherapy for DLBCL patients with R/R status were included. Meta-analyses of response rates, adverse events (AEs), overall survival (OS), and progression-free survival (PFS) were performed. The pooled event rates were calculated using a double arcsine transformation to stabilize the variances of the original proportions. Subgroup analysis was used to compare patients with different germinal center B-cell-like (GCB) phenotypes. Results: We included 11 publications that examined DLBCL patients with R/R status. These studies were published from 2008 to 2020. The cumulative objective response rate (ORR) for lenalidomide monotherapy was 0.33 (95% CI: 0.26, 0.40), and the ORR was better in patients with the non-GCB phenotype (0.50; 95% CI: 0.26, 0.74) than the GCB phenotype (0.06; 95% CI: 0.03, 0.11). The major serious treatment-related AEs were neutropenia, thrombocytopenia, respiratory disorders, anemia, and diarrhea. The median PFS ranged from 2.6 to 34 months and the median OS ranged from 7.8 to 37 months. Conclusion: This study provides evidence that lenalidomide monotherapy was active and tolerable in DLBCL patients with R/R status. Patients in the non-GCB subgroup had better responsiveness.